What Are the Preferences in Patient-Physician Communication Among Total Joint Arthroplasty Patients? - Siddhartha Dandamudi, BBA; Kyleen Jan, MD; Ilyass Majji, BS; Anne DeBenedetti, MSc; Omar Behery, MD, MPH; Brett R. Levine, MD, MS (Arthroplasty Today)
Background: Effective communication is essential in fostering a strong physician-patient relationship. With a growing number of patient engagement platforms, understanding communication preferences is crucial in guiding patient contact strategies more effectively. The goal of this study is to explore communication medium preferences of hip and knee arthroplasty patients. Methods: A 10-question survey focused on patient communication preferences with the surgical team was distributed anonymously to patients at clinic visits of multiple arthroplasty surgeons at a large academic center. No identifying information was collected. Results: Four hundred seventy-two responses were collected. Of the patients, 95.6% were willing to share their phone number with the surgical team. Of those responding, 53.5% and 35.4% indicated that a phone call and text, respectively, were their preferred communication medium. A majority (93%) of respondents had positive feelings towards receiving 1-way message updates with reminders, videos, and expected milestones perioperatively. Most patients (92.5%) want an open line of communication with the surgical team, and almost every respondent (99.6%) believes that the surgeon or insurance company is responsible financially for this means of communication or patient engagement platform. Conclusions: Our data suggest that direct communication via phone calls and texts are the preferred media of communication with arthroplasty patients. Financially, surgeons should be aware that engagement platforms may add to practice costs. However, incorporating these insights into practice can enhance patient satisfaction, ultimately leading to better outcomes and more efficient care. Understanding these preferences may afford clearer, more effective interactions with patients and potentially improve overall engagement and outcome data collection.